المواطنة والعمل الجمعوي - رقيق, عبد الله; عثماني, نعيمة (جامعة الوادي - University of Eloued, 2021)
أفرز الفكر الحديث مجموعة من المفاهيم الحضارية والحديثة في مقدمتها مفهوم المواطنة، هذا النتاج الفكري الإنساني النابع من تراكمات منجزات حضارية لأساليب الحياة العصرية هذا من جهة، ومن جهة أخرى نجد العمل الجمعوي الذي اصبح يحظى بأهمية كبيرة خصوصا في الآونة الاخير جراء جائحة كورونا، حيث شهد المجتمع تكافل كبير وكان لمختلف جمعيات المجتمع المدني فعالية على المستوى الميدان حتى وإن تعددت أشكالها وأنواعها و تباينت مستويات الاداء لكل منها. ومن خلال هذه الورقة البحثية سنحاول فك شفرات المواطنة من خلال ضبط مفهومها، وكيف يمكن تجسيدها في ظل العمل الجمعوي. Modern thought has produced a set of civilized and modern concepts, foremost of which is the concept of citizenship, this human intellectual product stemming from the accumulation of civilized achievements for this modern way of life on the one hand, and on the other hand we find the collective work that has become of great importance, especially in the recent times as a result of the Corona pandemic, where he witnessed Society is a great interdependence, and the various civil society associations were effective at the field level, even if their forms and types varied, and the performance levels for each of them varied. Through this research paper, we will try to decipher the codes of citizenship by adjusting its concept, and how it can be embodied in the light of collective action
Citizenship and associative action
مقال
Keywords: المواطنة، التطوع ، العمل الجمعوي; Citizenship, volunteering, associative work